(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The Seventh-day Adventist Church, despite its opposition to actively taking the life of a terminally ill patient, to suicide, and to facilitating a person’s suicidal plan, endorses the use of palliative care and painkiller, even though they can significantly accelerate the dying process. Its guidelines on the subject, Care for the Dying, were issued in 1992 and revised in 2013. The article analyzes this document and compares it with state legislations such as the Oregon’s law on dying with dignity of 1997 or the one foreshadowed by the judgement of the Italian Constitutional Court of 2019.